SOCIAL CONFLICT IN LAZUARDI'S LABYRINE NOVEL RED LANGIT SAGA BY GOLA GONG - Putra, Ari; Septia, Emil; Tatalita, Ricci Germani; Firdaus, Winci (Magistra Andalusia: Jurnal Ilmu Sastra, 2022)
This research is motivated by the novel of many social conflicts that occur in the community contained in the Blue Labyrinth, Langit Merah Saga is one of the novels that describe. This study aims to describe the social conflict in the novel Labirin Lazuardi Langit Merah Saga by Gola Gong. This type of research is qualitative research because the research data is in the form of text or words using descriptive analysis methods. The data of this research are in the form of words, sentence quotes and discourses about social conflict contained in the novel Labirin Lazuardi Langit Merah. Data was collected through the following steps: reading, marking and recording data, taking an inventory of all data related to social conflict. After that the data were analyzed and concluded the research results. The results of this study indicate that the social conflicts found are, First, personal conflicts or conflicts that occur between two individuals, such as conflicts between Blue and Cak Leman, Blue with Buto, Blue with Leo, Paijo with Butu, and Leo with Latief. Second, between the social classes, namely the conflict between the ruling class and the small people, the government class or state apparatus and the small people, the difference between the rich and the poor. Third, political conflict shows the interests of the apparatus in displacing the small people, the interests of the rulers and the interests of the government that do not side with the small people.